Simple, elegant pasta dinners : 75 dishes with inspired sauces - Marie, Nikki (Page Street Publishing Co., 2019)
Nikki Marie, blogger behind Chasing the Seasons, transforms everyone<U+2019>s go-to pantry staple by using heirloom Italian methods to create complex flavors at home. Creative combinations like French Onion Penne, Red Wine Spaghetti with Swiss Chard and Spinach and Avocado Linguine are ready faster than your go-to spaghetti and meatballs. It<U+2019>s easy to delight your weekend guests with Fresh Pumpkin Pappardelle with Browned Rosemary Butter or Fresh Chestnut Pasta with Sausage. Pasta is the perfect base for everything the seasons have to offer; use flavorful produce, tender meats and fresh seafood to make every pasta into a complete meal. Discover how versatile pasta can be, with options for light lunches, inspiration for leftovers and more. Sophisticated enough to impress at a dinner party and easy enough to throw together for a quick, satisfying family dinner, these dishes make pasta night more delicious than ever.